The intertwined relationships of power, justice and dependence. Issue 9 (2nd September 2014) - J. Hoppner, Jessica; A. Griffith, David; Yeo, ChangSeob
Abstract : Purpose: – The purpose of this study, drawing from exchange theory, is to examine how the intertwined relationships between power, justice and relative dependence influence relationship performance in buyer – seller relationships. Design/methodology/approach: – A two-wave structural equation model with latent variable interactions was estimated on a dataset of 283 buyer – seller relationships. Findings: – Exercised coercive and reward power follow different processes, direct and indirect, to influence relationship performance. The use of coercion was found to be substantively more detrimental to the buyer – seller relationship than the use of rewards were beneficial. Relative dependence tempers the negative influence of coercion. Research limitations/implications: – Managers of buyer – seller relationships need to be judicious in their use of coercion and rewards. In their efforts to manage relationship performance, whenever possible, managers should seek to avoid punishing their partner more so than they should seek to reward them. Originality/value: – Although proposed under a single theoretical perspective, power and justice have developed as separate streams within the extant literature. Examining these constructs together can increase the current understanding of how to manage buyer – seller relationships.